Meeting institutional criteria for social resilience: a nested risk system model - Blair, Berill; Lovecraft, Amy L.; Kofinas, Gary P. (Resilience Alliance, 2014)
Communities of Alaska’s North Slope face increased stresses from cumulative effects of industrial development, resource use, and changing cryospheric and socioeconomic conditions. Given these multiple pressures, what avenues exist for citizens and decision makers to exchange knowledge about impacts of oil resource extraction in Alaska, and how do the successes and failures of knowledge exchange affect the resilience of the local social ecological system? We focused our research on the risk management process of Alaska North Slope oil resources, drawing on literature that has grown out of the risk society thesis and concepts of resilience science. We surveyed state and federal initiatives designed to increase local and indigenous stakeholder engagement in science and policy issues because such guidelines and regulations impact on the abilities of local peoples and communities to adapt sustainability strategies. Perceived risks and desired outcomes of stakeholders on the front lines of climate change and resource development should inform regulations that aim to anticipate future impacts and needed adaptation strategies. Integration of local values and perceptions in an adaptive risk management approach is fundamental in resilience-based ecosystem stewardship. The three case studies we have presented show that current provisions fail to equitably include the local and indigenous knowledge of Alaska’s North Slope Borough communities in environmental risk mediation in proportion to the scope of risks inherent in current oil development policies. Our findings underscore the need for new, proactive risk management strategies that build on local stakeholders’ rationalities on the trade-offs of risks and opportunities.